2021
DOI: 10.1177/20503121211023367
|View full text |Cite
|
Sign up to set email alerts
|

Individual, socio-cultural, and health facility factors affecting men’s involvement in facility-based childbirth in Southwest, Ethiopia: A mixed method study

Abstract: Introduction: Traditionally, men are not supposed to take part in maternal health issues in many cultures. Nevertheless, pregnancy care and childbirth are the most crucial matters of reproductive health influenced by men. Hence, the aim of this study was to identify individual, sociocultural, and health facility factors affecting men’s involvement in facility-based childbirth in Southwest, Ethiopia. Objectives: The aim of this study was to identify individual, sociocultural, and health facility factors affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The data collection tool was developed by reviewing related literature. 15 , 19 , 20 , 22 Data were collected using semi-structured, pretested questionnaires through face-to-face interview. The questionnaire contains socio-demographic characteristics, obstetric and maternal health services utilization related characteristics, decision-making autonomy, and intimate partner violence-related questions, and questions assessing husband involvement in MNCH service.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data collection tool was developed by reviewing related literature. 15 , 19 , 20 , 22 Data were collected using semi-structured, pretested questionnaires through face-to-face interview. The questionnaire contains socio-demographic characteristics, obstetric and maternal health services utilization related characteristics, decision-making autonomy, and intimate partner violence-related questions, and questions assessing husband involvement in MNCH service.…”
Section: Methodsmentioning
confidence: 99%
“… 18 Studies conducted in Ethiopia showed that husband involvement in ANC care were 61% and 36.5% of husbands involved during labor and delivery. 19 , 20 Also study conducted in Gondar city showed that 40.1% of male involved in HIV counseling and testing during antenatal care follow up. 21 Studies conducted in different countries suggest different factors associated with husband involvement in MNCH care, like; women's level of education, husband educational status, number of children, average family income, occupation of husband, decision making autonomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Anuak sustain on crop production, fishing, and hunting; the Nuer are mainly pastoralists dependent on livestock rearing. The most recent population-based HIV impact assessments documented that Gambella had the highest HIV prevalence in Ethiopia (5.7%) when the study was conducted [30].…”
Section: Study Settingmentioning
confidence: 99%
“…The health officers never conduct an activity to increase the participation of husbands because there are heavy challenges that must be faced besides having no budget allocation for such an activity. mentioned by Hailemariam [15]. Among them is the cultural view that husbands are not usually involved in matters that have long been women's affairs.…”
Section: Researchermentioning
confidence: 99%